Morphological and molecular identification of biologically active endophytic fungi isolated from Dillenia indica L. - Zinnurine, Rabita; Sohrab, Md Hossain; Afroz, Farhana; Rony, Satyajit Roy; Akhter, Shammi; Begum , Mst Nadira; Rana , Md Sohel (Bangladesh Journal of Plant Taxonomy, 2024)
This study reported the broad spectrum endophytic variety from the elephant apple Dillenia indica L. Endophytes are microorganisms lying within the plant interior tissues, lasting as the whole or part of their life cycle without causing any conspicuous symptoms of infection to host plants. Surface sterilization of leaves and stems was the basic doing work to isolate endophytic fungi. 16 isolates were identified and grouped into 7 based on of morphological characteristics. Through morphological colony, all the isolated strains were identified up to genus level. Isolated seven fungi, 6 from the leaves part and 1 from the bark part were subjected to sequence analysis of internal transcribed spacer (ITS) gene. Finally, seven well-known species named Colletotrichum Siamense, Phomopsis liquidambaris, Diaporthe perseae, Fusarium incarnatum, Colletotrichum falcatum, and Lasiodiplodia theobromae were identified compared with the Basic Local Alignment Search Tool (BLAST) results analysis. This study provides the broad theory of the interrelation of morphological and molecular homologies for the identification of prospective bioactive fungi for further study and experiment so that those fungus acts as a catalyst for novel thinking and the discovery of drug molecules for the welfare of mankind. Bangladesh J. Plant Taxon. 31(2): 311-320, 2024 (December)